ANALISIS MARKETING MIX DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PADA UKM BANANA POP KOTA BIMA - Nurul Aulia; Intisari Haryanti; Sri Ernawati (MANAJEMEN DEWANTARA, 2023)
This study aims to determine the marketing mix and to find out the obstacles in implementing the marketing mix and to find out how the brand image of Banana Pop SMEs (Small and Medium Enterprises) products in Bima City. In addition, this study also aims to find out which of the two variables has the most influence on consumer decisions in buying products from Banana Pop SMEs Bima City. The type of research in this study is associative with the research instrument using a questionnaire with a Likert scale. The sampling technique used in this research is accidental sampling. Data collection techniques were carried out by observation, distribution of questionnaires and literature study. The research results obtained in this study are that in the Marketing Mix variable there are obstacles that arise from the Price indicator, while in the Purchase Decision variable there are obstacles from the Information Search indicator.